The Chilean Network of Innovation Researchers (GESTIÓN Y TENDENCIAS, 2019)
In order to collaborate with policy makers, business leaders, local and national government, and society as a whole, a group of researchers established the Chilean Network of Innovation Researchers in early 2019. The network seeks to address in an integrated way the challenges of exchanging and creating knowledge about innovation in the country, contributing to innovation management in all types of organizations, and supporting the development of science, technology, and innovation policy.